A cooperative framework for optimizing transboundary hydropower development. Issue 8 (17th November 2017) - Bhagabati, Seemanta Sharma; Kawasaki, Akiyuki; Babel, Mukand Singh
ABSTRACT: Hydropower development may result in water conflicts among the riparian nations, which, however, can be resolved by benefit sharing. An optimization framework is proposed for a transboundary sub-basin following a cooperative game theoretical approach. A broad range of factors at different levels of cooperation between the riparian countries has been used in the optimization model. As an illustration, the framework is implemented in the Sesan and Sre Pok sub-basins of the Lower Mekong Basin. Higher levels of cooperation lead to greater total net benefits as well as greater benefits to individual countries.